Dosimetry in differentiated thyroid carcinoma. Issue 1 (13th December 2012) - Mínguez, Pablo; Genolla, José; Celeiro, José Javier; Fombellida, José Cruz
Abstract : Purpose: : The aim of this study has been to perform a dosimetric study in the treatments of differentiated thyroid cancer (DTC) performed in our center in order to find a dose–effect correlation. Methods: : Thirty patients treated for DTC with 3700 MBq of 131 I have been included in this study. For reasons of radiological protection all of them spent two nights as inpatients. Dose rate at 1 m from all patients was measured approximately 20 and 44 h after the administration of the radioiodine and a whole body scan in the gamma camera was performed approximately 1 week later. With those measurements and by using a model of two compartments the activities in thyroid bed remnants and in the whole body were calculated as a function of time. The integration of both activities yields the corresponding cumulated activities. Absorbed doses to thyroid bed remnants and to the whole body can be calculated following the MIRDOSE method—that is, by multiplying the corresponding cumulated activities by the corresponding S factors. Results: : The absorbed doses to thyroid bed remnants calculated in this study fall into a very wide range (13–1161 Gy) and showed the highest correlation factors with the following parameters: the absorbed dose rate to thyroid bed remnants, the cumulated activity in thyroid bed remnants, and the maximum radioiodine uptake in thyroid bed remnants. The absorbed doses to the whole body range from 0.12 to 0.23 Gy. The ablation was successful in all patients, and in spite of the wide range of absorbed doses to thyroid bed remnants obtained, no dose–effect correlation could be obtained. Conclusions: : Facing DTC treatments from a dosimetric viewpoint in which a predosimetry to calculate the activity of 131 I to be administered is performed is a subject difficult to handle. This statement is based on the fact that although a very wide range of absorbed doses to thyroid bed remnants was obtained (including several absorbed doses well below some dose thresholds previously published to achieve ablation of thyroid bed remnants), ablation of thyroid bed remnants was successful for all patients and therefore no dose–effect correlation could be determined.